THE ROLE OF EDUCATORS AND THE INFLUENCE OF FINANCIAL BEHAVIOR ON PERSONAL FINANCIAL DISTRESS AMONG UNDERGRAD STUDENTS OF PUBLIC UNIVERSITIES IN SABAH, MALAYSIA - Nelson Lajuni; Imbarine Bujang; Abdul Aziz Karia; Yusman Yacob, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Abstract: The issues of financial mismanagement among youths has been growing at an alarming rate lately as reported by The Malay Mail Online in 2016 that on average eleven youth declared bankrupt every day, therefore, immediate corrective measures need to be identified on whether the roles of educators and change in financial behavior may lead to the solution to this problem. The purpose of this work is to analyze the role of educators and the influence of financial behavior towards personal financial distress of undergrads in Sabah, Malaysia. Five hundred copies of questionnaires were disseminated, however, only four hundred and fifty-four usable copies were subsequently called up and deemed usable after the data cleaning process. The data were then analyzed using Partial Least Squares-Structural Equation Modelling. Common method variance and non-response bias were checked statistically and addressed. The results suggest that educators and financial behavior influence were able to explain and predict personal financial distress of undergrads students in Sabah, Malaysia. As more and more youth entangle with financial mismanagement nowadays, this work offers contribution to the literature by offering insights into the field of personal financial distress of undergrads that could help stakeholders to take necessary steps to tackle this matter the right way.